MENINGKATKAN KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING - Kusumah, Airlangga Wirabagja; Usada, Wisnu; Permana, Aditya (IKIP Siliwangi, 2019)
There are several factors experienced by students in learning, among others, the limited ability of students to develop ideas or ideas into a form of writing, the use of spelling and punctuation that is still wrong. The formulation of the problem from this study are: 1) How can the influence of Discovery Learning improve the ability to write students? 2) What are the obstacles experienced by students in improving their writing skills? The purpose of this study was to determine the effect of the Discovery Learning learning model on Indonesian subjects about the procedure text. This research was conducted at Sangkuriang 1 Cimahi Vocational School using a quantitative approach. The data of this study used the One-Group design type pretest-posttest Design which was conducted in class XI BDP with the Procedure Text material. One-Group pretest-posttest Design in this experiment had a pretest that before being given treatment, the results of the treatment could be more accurate than those not treated. The results of the study indicate that the most increase in writing procedure text at the initial value (pretest): the lowest value of the student gets 50 and the highest score of the student gets 80 whereas, after using the Discovery Learning model, the final value of the student (posttest): the lowest value the student gets 70 and the highest score of students gets 85.